DEVELOPMENT STRATEGIES AND TRANSFORMATION OF THE REGION’S INDUSTRIAL COMPLEX - Grozova, Olga; Tsvetkova, Galina; Maslikhina, Veronika (Journal of Applied Engineering Science, 2020)
The aim of the study is to analyze the industrial complex transformation of the provincial region and determine the prospects for its development. The economic potential of industrial complex of the Mari El Republic of Russia is analyzed. The structural and dynamic analysis of the region’s manufacturing industry, as well as the analysis of its material and technical base, investment, innovation and human resources is carried out. High depreciation of fixed assets of industry prevents its successful transformation. The high impact of the investment level on the growth rate of the manufacturing industry has been revealed. The low level of region’s innovative potential has no impact on the manufacturing industry development. The personnel potential of the region’s industry is characterized by the outflow of personnel with higher education and the availability of personnel with labour occupations. The development strategies of the region’s industrial complex are considered. High-tech enterprises of the region (IT-sphere, enterprises for the electrical equipment production, electronic and optical equipment production) can implement an offensive strategy of innovative development. The intermediate strategy and import substitution strategy are substantiated as actual strategic decisions for the enterprises of medium and low-tech industry sectors. They can provide competitive positions of the region’s industry.